2015
DOI: 10.1002/arch.21240
|View full text |Cite
|
Sign up to set email alerts
|

GLUTATHIONE S‐TRANSFERASE Genes IN THE RICE LEAFFOLDER, Cnaphalocrocis medinalis (LEPIDOPTERA: PYRALIDAE): IDENTIFICATION AND EXPRESSION PROFILES

Abstract: In insects, glutathione S-transferases (GSTs) play critical roles in the detoxification of various insecticides, resulting in insecticide resistance. The rice leaffolder, Cnaphalocrocis medinalis, is an economically important pest of rice in Asia. GST genes have not been largely identified in this insect species. In the present study, by searching the transcriptome dataset, 25 candidate GST genes were identified in C. medinalis for the first time. Of these, 23 predicted GST proteins fell into five cytosolic cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 48 publications
(71 reference statements)
4
24
0
Order By: Relevance
“…In B. dorsalis , the expressions of multiple GST genes were increased by β‐cypermethrin, suggesting that the GST gene may function in detoxifying β‐cypermethrin . In contrast, the mRNA transcript of the remaining GST gene CpGSTe1 was decreased after treatment with a LD 10 of λ ‐cyhalothrin for 3–12 h. Down‐regulated expression of GST genes has been also reported in P. xylostella , N. lugens , C. medinalis , and L. decemlineata after exposure to insecticides . Down‐regulation of a subset of GSTs may be an adaptive mechanism in insects for reducing the total enzymatic activity of GST enzymes to prevent exhausting the supply of GSH .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In B. dorsalis , the expressions of multiple GST genes were increased by β‐cypermethrin, suggesting that the GST gene may function in detoxifying β‐cypermethrin . In contrast, the mRNA transcript of the remaining GST gene CpGSTe1 was decreased after treatment with a LD 10 of λ ‐cyhalothrin for 3–12 h. Down‐regulated expression of GST genes has been also reported in P. xylostella , N. lugens , C. medinalis , and L. decemlineata after exposure to insecticides . Down‐regulation of a subset of GSTs may be an adaptive mechanism in insects for reducing the total enzymatic activity of GST enzymes to prevent exhausting the supply of GSH .…”
Section: Discussionmentioning
confidence: 89%
“…35 In contrast, the mRNA transcript of the remaining GST gene CpGSTe1 was decreased after treatment with a LD 10 of -cyhalothrin for 3-12 h. Down-regulated expression of GST genes has been also reported in P. xylostella, N. lugens, C. medinalis, and L. decemlineata after exposure to insecticides. [41][42][43][44] Down-regulation of a subset of GSTs may be an adaptive mechanism in insects for reducing the total enzymatic activity of GST enzymes to prevent exhausting the supply of GSH. 44 These results indicate that these up-regulated GST genes may be involved in detoxification of -cyhalothrin in C. pomonella.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether this characteristic was shared with the other members of the subclade, we first searched for SP in the sequence of AtraGST (Leal et al, 2009), MsexGST-msolf (Robertson et al, 1999; Rogers et al, 1999), CsupGSTd1 (Liu et al, 2015a) and CmedGSTd1 (Liu et al, 2015b) and we indeed identified putative SPs for all them. We then completed by bioinformatics the N-terminus sequences for the 5 other genes from this clade ( SfruGSTd2, HarmGSTd02, BmGSTd1, EposGST11 , and PxylGSTd1 ) and we also identified predicted SP for each of them.…”
Section: Resultsmentioning
confidence: 98%
“…In S. littoralis , epsilon clade accounts for almost half of the described sequences, with various expression patterns ranging from ubiquitous to antennal enriched genes. SlitGSTe clustered with lepidopteran GSTe functionally involved in insecticide conjugation and protection against oxidative stress in B. mori, H. armigera, S. litura , and S. exigua (Huang et al, 2011; Yamamoto et al, 2013; Liu et al, 2015b; Xu et al, 2015; You et al, 2015; Zhou et al, 2015; Wan et al, 2016; Zhang et al, 2016; Hirowatari et al, 2017; Labade et al, 2018). Moreover, three P. xylostella GSTe are also preferentially expressed in the antennae (He et al, 2017), suggesting a potential role in olfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation